2020
DOI: 10.1590/1806-9061-2019-1189
|View full text |Cite
|
Sign up to set email alerts
|

Dried Cassava Residue in Laying Quail Feeding

Abstract: This study evaluated the performance, egg quality, relative weight of the gastrointestinal organs, and the intestinal morphometry of laying quails fed diets containing levels of dried cassava residue (DCR). A total of 120 150-day-old Japanese quails were distributed in a completely randomized design with five treatments (0.0; 2.5; 5.0; 7.5; and 10.0% of DCR), four replicates, and six birds per experimental unit. The dietary inclusion of DCR did not affect (p>0.05) performance, internal egg quality, yolk color,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Based on these observations, it is apparent that cassava meal could be used to completely replace maize in diets of quails, however, the meal is more potent in enhancing the performance indices of quails at 75% dietary replacement level. The reports of Almeida et al (2020) also showed that a 10% dietary inclusion of the dried cassava residue did not impair the growth performance of laying quails. At a 60% replacement level, dietary sorghum resulted in increased final body weight and feed intake in Japanese quails, however, the values recorded were comparable to the quails fed with the control diet (Khaleel et al, 2021).…”
Section: Effect Of Energy Sources On Production Health and Meat Quali...mentioning
confidence: 89%
See 3 more Smart Citations
“…Based on these observations, it is apparent that cassava meal could be used to completely replace maize in diets of quails, however, the meal is more potent in enhancing the performance indices of quails at 75% dietary replacement level. The reports of Almeida et al (2020) also showed that a 10% dietary inclusion of the dried cassava residue did not impair the growth performance of laying quails. At a 60% replacement level, dietary sorghum resulted in increased final body weight and feed intake in Japanese quails, however, the values recorded were comparable to the quails fed with the control diet (Khaleel et al, 2021).…”
Section: Effect Of Energy Sources On Production Health and Meat Quali...mentioning
confidence: 89%
“…There is a dearth of literature on the effect of energy sources on gut microbiota in quails. However, the study of Almeida et al (2020) revealed that the villi height, crypt depth and villi height/ crypt depth ratio of quails fed with varying dietary levels (2.5, 5, 7.5, 10%) of dried cassava residue did not differ from those that were fed with the control diet, suggesting that the different dietary levels of the dried cassava residue did not compromise the integrity of the intestinal epithelium in the birds. Nonetheless, future research should investigate the effect of alternative energy sources on gut microbiota of quail and other poultry species.…”
Section: Effect Of Alternative Energy Sources On Gut Microbiotamentioning
confidence: 94%
See 2 more Smart Citations
“…The plant originates from South America and was introduced to Africa in the sixteenth century to which it outcompeted some of the local crops as a staple crop in Africa [ 85 ]. Several studies have reported that 10–50% inclusion of dried cassava meal in place of maize in layer or broiler quail diets do not compromise the productive performance of the birds [ 84 , 86 ]. Africa is the largest producer of cassava [ 87 , 88 ], but this crop has not been adopted as a major feed ingredient in poultry diets because of the presence of anti-nutritional factors such as hydrocyanic acids [ 89 ].…”
Section: Nutritional Strategies To Promote a Sustainable And Profitable Quail Businessmentioning
confidence: 99%